Fabrication, Applications, and Prospects of Aramid Nanofiber. (20th March 2020) - Yang, Bin; Wang, Lin; Zhang, Meiyun; Luo, Jingjing; Lu, Zhaoqing; Ding, Xueyao
Abstract: Aramid nanofibers (ANFs) are of great interest in various applications due to its 1D nanoscale, high aspect ratio, high specific surface area, excellent strength, and modulus as well as impressive chemical and thermal stabilities. It is considered as one of the most promising nano‐sized building blocks with excellent properties and has therefore drawn increasing attention since 2011. However, no review has summarized the research progress and the prospective challenges of ANF. Herein, the methods of ANF fabrication and their relative merits are comprehensively discussed together with the challenges and progress in the deprotonation method for preparing ANF. The fabrication methods and development of ANF‐based advanced materials with different macroscopic morphologies, including the 1D ANF aerogel fiber, 2D ANF film/nanopaper/coating, and 3D ANF gel and particle are also described. Furthermore, the applications of ANF in nanocomposite reinforcement, battery separators, electrical insulation nanopaper, flexible electronics, and adsorption and filtration media are presented. Additionally, the possible challenges and outlooks toward the future development of ANF are highlighted. This review indicates that the ANF and ANF‐based materials mentioned herein will boost the development of next‐generation advanced functional materials. Abstract : Aramid nanofibers (ANFs) present unique properties as a promising building block for the construction of advanced materials. Herein, the fabrication methods, properties, development, and applications of ANF in different forms are summarized. The possible challenges in and outlooks toward the future development of ANF and ANF‐based nanocomposites are highlighted.